2022
DOI: 10.3389/fpsyt.2022.857087
|View full text |Cite
|
Sign up to set email alerts
|

A narrative review of the epigenetics of post-traumatic stress disorder and post-traumatic stress disorder treatment

Abstract: Epigenetic research in post-traumatic stress disorder (PTSD) is essential, given that environmental stressors and fear play such a crucial role in its development. As such, it may provide a framework for understanding individual differences in the prevalence of the disorder and in treatment response. This paper reviews the epigenetic markers associated with PTSD and its treatment, including candidate genes and epigenome-wide studies. Because the etiopathogenesis of PTSD rests heavily on learning and memory, we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 131 publications
0
4
0
Order By: Relevance
“…Most recently, in 2023, Wilker et al found that methylation on the cg25535999 CpG site of the NR3C1 intron is negatively associated with PTSD symptoms (however, this study lacks data on GR expression level) [62]. Other epigenetic markers have been proposed to be associated with recovery or the prediction of treatment response [36,[63][64][65][66][67][68][69]. Lastly, in 2021 Vinkers et al revealed the possibility of reversing DNA methylation at the ZFP57 gene as a treatment for PTSD, opening the window to a new method of PTSD and psychiatric disorder treatment via epigenetics [36].…”
Section: Future Directions and Usementioning
confidence: 96%
“…Most recently, in 2023, Wilker et al found that methylation on the cg25535999 CpG site of the NR3C1 intron is negatively associated with PTSD symptoms (however, this study lacks data on GR expression level) [62]. Other epigenetic markers have been proposed to be associated with recovery or the prediction of treatment response [36,[63][64][65][66][67][68][69]. Lastly, in 2021 Vinkers et al revealed the possibility of reversing DNA methylation at the ZFP57 gene as a treatment for PTSD, opening the window to a new method of PTSD and psychiatric disorder treatment via epigenetics [36].…”
Section: Future Directions and Usementioning
confidence: 96%
“…Cognitive Systems: Cognitive de cits in PTSD affect attention, planning, and memory, with attentional bias towards threat stimuli and memory biases contributing to hyperarousal [21]. Epigenetic modi cations and gene polymorphisms, like in the glucocorticoid receptor (GR) gene, are linked to memory de cits in PTSD [22], [23]. Effective treatment may improve cognitive de cits.…”
Section: Building Of Dictionariesmentioning
confidence: 99%
“…Cognitive deficits in PTSD affect attention, planning, and memory, with attentional bias towards threat stimuli and memory biases contributing to hyperarousal [28]. Epigenetic modifications and gene polymorphisms, like in the glucocorticoid receptor (GR) gene, are linked to memory deficits in PTSD [29,30]. Effective treatment may improve cognitive deficits.…”
Section: Cognitive Systemsmentioning
confidence: 99%